Social media as a trigger for the 2011 Chilean student movement - Sola-Morales, Salomé (2015)
This article studies the role social media played in the Chilean student movement during 2011; specifically in the period of greater activity for this group (June, July, and August). This paper is mainly about raising questions regarding the use of social media by the main student federations, as key movement actors. In order to do that, this case study firstly proposes a conceptual framework to better understand the Chilean student movement in a Latin-American context and, secondly, it also includes an empirical analysis about the use of different on-line platforms (Facebook, federations’ media, Twitter, and Youtube). Special attention is paid to the dynamics of strengthening identities, the spread of political ideas and to student movement evolution in the net.